OCT Application for Sterile Corneal Graft Screening in the Eye Bank - Quintin, Adrien; Hamon, Loïc; Mäurer, Stephanie; Langenbucher, Achim; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2021)
Background and Objective Sterile donor tomography enables the detection of corneal tissues with refractive anomalies. The aim of this study was to determine the curvature and thickness of donor corneas to support proper selection in the eye bank.Methods 704 donor corneas (Klaus Faber Center, LIONS Eye Bank Saar-Lor-Lux, Trier/Westpfalz, in Homburg/Saar) were measured using the anterior segment optical coherence tomograph (AS-OCT) CASIA 2 (Tomey Corp., Nagoya, Japan). The corneoscleral discs were measured in their cell culture flask, which was positioned in a holder on the chin rest of the AS-OCT, after conversion to medium II (with 6% dextran T-500). The measured raw data were analysed and processed in MATLAB (MathWorks Inc., Natick, Massachusetts, USA), after which the refractive power of the steep and flat meridian at the anterior and posterior surface and the central corneal thickness (CCT) of the donor corneas were determined. Results values are expressed as mean x̅ ± standard deviation SD.Results The mean refractive power of the steep/flat meridian at the anterior surface was 45.4 ± 1.8 D/44.0 ± 1.3 D, the corresponding values for the posterior surface were − 6.2 ± 0.3 D/− 5.9 ± 0.2 D, and the mean CCT was 616.3 ± 85.1 µm. Of the 704 (100%) measured donor tissues, 590 (83.8%)/670 (95.2%) donor corneas showed no anomaly beyond respectively x̅ ± 2 SD/x̅ ± 3 SD among the 5 examined parameters. 72 (10.3%)/23 (3.3%) donor corneas had only 1 anomaly, 26 (3.7%)/10 (1.4%) had 2 anomalies, 10 (1.4%)/1 (0.1%), 3 anomalies, 5 (0.7%)/0 (0.0%), 4 anomalies, and 1 (0.1%)/0 (0.0%), 5 anomalies.Conclusions AS-OCT provides an objective and sterile screening method to identify corneal tissues with curvature anomalies in order to further optimise donor selection in the eye bank. To avoid postoperative refractive surprises, donor corneas with a total refractive power that deviates > ± 3 SD from the mean should not be used for penetrating or anterior lamellar keratoplasty, but may be suitable for posterior lamellar keratoplasty (DMEK or DSAEK). In the future, sterile donor tomography could enable: (1) the harmonisation of donor and recipient tomography, which may minimise residual astigmatism for a particular donor-recipient pair; and (2) the improvement of IOL power calculation in a classical triple procedure by means of regression analysis between pre- and postoperative total refractive power of corneal grafts.Hintergrund und Ziel Die sterile Spendertomografie ermöglicht die Erkennung von Hornhautgeweben mit refraktiven Anomalien. Ziel dieser Studie war es, die Krümmungs- und Dickenwerte von Spenderhornhäuten zur Selektionsunterstützung in der Hornhautbank zu bestimmen.Methoden Vermessungen von 704 Spenderhornhäuten (Klaus-Faber-Zentrum für Hornhauterkrankungen inkl. LIONS Hornhautbank Saar-Lor-Lux, Trier/Westpfalz, in Homburg/Saar) wurden mithilfe des optischen Kohärenztomografen des vorderen Augenabschnittes (VAA-OCT) CASIA 2 (Tomey Corp., Nagoya, Japan) durchgeführt. Messungen der Spenderhornhäute erfolgten durch ihre Zellkulturflasche, die in einer mit 3D-Drucker (Ultimaker 2 Go, Ultimaker B. V., Geldermalsen, Niederlande) hergestellten Halterung auf die Kinnstütze des VAA-OCT positioniert wurde, nach Umstellung des Hornhautgewebes in Medium II (mit 6% Dextran T-500). Die vermessenen Rohdaten wurden in MATLAB (The MathWorks Inc., Natick, Massachusetts, USA) analysiert und verarbeitet, woraufhin die Brechkraft im steilen und flachen Meridian der Vorder- und Rückfläche sowie die zentrale Hornhautdicke der Spenderhornhaut bestimmt wurden. Ergebniswerte werden als Mittelwert x̅ ± Standardabweichung SD angegeben.Ergebnisse Die Brechkraft des steilen/flachen Meridians der Vorderfläche betrug 45,4 ± 1,8 dpt/44,0 ± 1,3 dpt, die entsprechenden Werte für die Rückfläche waren − 6,2 ± 0,3 dpt/− 5,9 ± 0,2 dpt. Die mittlere zentrale Hornhautdicke betrug 616,3 ± 85,1 µm. Jenseits x̅ ± 2 SD/x̅ ± 3 SD wiesen von den 704 (100%) gemessenen Spendergeweben 590 (83,8%)/670 (95,2%) Spenderhornhäute unter den 5 untersuchten Parametern keine Anomalie auf. 72 (10,3%)/23 (3,3%) Spenderhornhäute wiesen nur 1 Anomalie, 26 (3,7%)/10 (1,4%) 2 Anomalien, 10 (1,4%)/1 (0,1%) 3 Anomalien, 5 (0,7%)/0 (0,0%) 4 Anomalien und 1 (0,1%)/0 (0,0%) 5 Anomalien auf.Schlussfolgerungen Das VAA-OCT bietet eine objektive und sterile Screeningmethode zur Identifikation von Hornhautgewebe mit Krümmungsanomalien, um die Spenderauswahl in der Hornhautbank weiter zu optimieren. Um postoperative refraktive Überraschungen zu vermeiden, sollten Spenderhornhäute mit einer > ± 3 SD vom Mittelwert abweichenden Gesamtbrechkraft idealerweise nicht für eine perforierende oder anteriore lamelläre Keratoplastik verwendet werden. Diese Gewebe können jedoch für eine hintere lamelläre Keratoplastik wie die DMEK oder DSAEK geeignet sein. In Zukunft könnte die sterile Spendertomografie Folgendes ermöglichen: (1) die Harmonisierung von Spender- und Empfängertomografie, wodurch der Restastigmatismus für ein bestimmtes Spender-Empfänger-Paar minimiert werden kann; und (2) die Verbesserung der Kunstlinsenberechnung bei klassischer Triple Procedure durch die Regressionsanalyse zwischen prä- und postoperativer Gesamtbrechkraft des Spenderhornhautgewebes.
Keywords: optical coherence tomography; sterile donor tomography; donor cornea; eye bank; keratoplasty